Effectiveness of Fiscal Incentives for R and D : Quasi-Experimental Evidence - Guceri, Irem.; Liu, Li. (Washington, D.C. : International Monetary Fund, 2017)
With growing academic and policy interest in research and development (R and D) tax incentives, the question about their effectiveness has become ever more relevant. In the absence of an exogenous policy reform, the simultaneous determination of companies' tax positions and their R and D spending causes an identification problem in evaluating tax incentives. To overcome this identification challenge, we exploit a U.K. policy reform and use the population of corporation tax records that provide precise information on the amount of firm-level R and D expenditure. Using difference-in-differences and other panel regression approaches, we find a positive and significant impact of tax incentives on R and D spending, and an implied user cost elasticity estimate of around -1.6. This translates to more than a pound in additional private R and D for each pound foregone in corporation tax revenue.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet